The impact of employee rewards on employee motivation: Toxic environment as a moderating variable - Mdhlalose, Dickson (Journal of Economics and Business Letters, 2025)
Employee rewards are crucial for motivating and recognizing organizational contributions. However, organizations frequently overlook the elements (financial and non-financial rewards) that motivate employees. Most organizations lack tools and tactics to motivate employees, and the worst part is that a toxic work environment demotivates employees. This study aimed to investigate and understand how employee rewards affect motivation in a toxic environment as a moderating variable. Exploratory research was conducted for this review. Information was gathered from online publications, dissertations, online databases, and books relevant to the topic. Financial benefits are the most effective motivator for most employees; however, selected individuals are driven by intrinsic rewards. Money alone is not always sufficient to motivate employees. Regardless of these benefits, a hostile work environment motivates employees. To foster a healthy work environment, organizations must train managers and staff in professionalism, fairness, positivism, and workplace culture. Employees or managers acting toxically toward other staff members should be addressed immediately. This study emphasizes the value of reward systems in a nontoxic workplace. Organizations can promote greater job satisfaction, which in turn lowers absenteeism and increases employee motivation levels, ultimately boosting total economic production by eliminating the toxic aspects that may impair motivation.